Innovation and Intrinsic Motivation of Generation Z in the Coffee Shop Industry: A Study in Sidoarjo - Rizki Aria Putra; Rifdah Abadiyah; Vera Firdaus Firdaus (Perkumpulan Dosen Muda (PDM) Bengkulu, 2026)
Purpose: This study examines the influence of the work environment, employee innovation, and intrinsic motivation on employee performance in coffee shops located in the Sidoarjo DPR Plot Area. Methodology: A quantitative research design was employed using a survey method with a sample of 96 respondents, determined through cluster sampling. Data were collected using a Likert-scale questionnaire and analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM). Results: The results indicate that the work environment (β = 0.226; p = 0.003), employee innovation (β = 0.300; p < 0.001), and intrinsic motivation (β = 0.314; p = 0.048) have a positive and significant effect on employee performance. The coefficient of determination shows that the model explains 79.4% of the variance in employee performance (R² = 0.794). Findings: These findings highlight the importance of creating a supportive work environment, fostering innovation, and strengthening intrinsic motivation to enhance employee performance in the coffee shop industry. Novelty & Originality: This study contributes to the human resource management literature by providing empirical evidence from the creative culinary sector at the regional level. Conclusions: The study concludes that integrated efforts to improve work environment, innovation, and motivation are essential for optimizing employee performance. Type of Paper: This paper is an empirical research paper.